STRATEGI PEMBELAJARAN HUMANISTIK DALAM MENINGKATKAN MOTIVASI INTRINSIK PESERTA DIDIK PADA MATA PELAJARAN PAI: STUDI KASUS DI SMP AL-KAUTSAR PALEMBANG - Popy Indar Sari; Larasati; Fitrioviyanti; Ienymarlina (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine the implementation of humanistic learning strategies in enhancing the intrinsic motivation of students in Islamic Religious Education (PAI) subject at SMP Al-Kautsar Palembang. The humanistic approach positions students as active subjects who possess the potential to develop optimally through meaningful learning experiences. The research method employed is descriptive qualitative with a case study approach. Data were collected through participatory observation, in-depth interviews, and documentation studies. Research subjects consisted of PAI teachers, students from grades VII-IX, and the principal of SMP Al-Kautsar Palembang. The results show that the implementation of humanistic learning strategies—including experiential learning, student-centered learning, creating a conducive classroom climate, and fulfilling students' psychological needs—significantly increases their intrinsic motivation in learning PAI. Indicators of increased intrinsic motivation are evident from greater active questioning, enthusiasm in discussions, independent learning, and students' curiosity toward PAI content. This study recommends that PAI teachers consistently integrate humanistic principles in the learning process to nurture a generation that is faithful, knowledgeable, and morally sound